Reformulation of School Management Strategies in Improving Teachers Digital Competence: A Case Study - Suparno, Suparno; Pujianto, Eko (Juwara: Jurnal Wawasan dan Aksara, 2025)
This research aims to explore and analyze the reformulation of school management strategies in improving the digital competence of teachers in private high schools. Digital competence is an urgent need in the era of educational transformation, especially for teachers as the main actors in the learning process. This study uses a qualitative approach with a case study design on two private high schools located in the Magetan area. Data were collected through in-depth interviews, participatory observations, and documentation studies, analyzed using the Miles and Huberman model which included data reduction, data presentation, and conclusions drawn. The results of the study show that private schools that implement HR strategies in a planned and contextual manner ranging from digital skill-based teacher recruitment, continuous training, digital platform-based performance evaluation, to providing digital innovation-based incentives are more successful in improving teacher competence. The transformational leadership of the principal is a key factor in the success of the strategy. These findings confirm the importance of a comprehensive school management reformulation to support the successful digital transformation of education in private secondary schools. This research provides theoretical and practical implications for school and foundation management in designing digital needs-based human resource strategies.